The impact of celebrity endorsement on customers buying behaviour towards millennials in Melaka Tengah / Farith Azizi Mohayyaddin Abdul Kader - Mohayyaddin Abdul Kader, Farith Azizi (Faculty of Business and Management, 2018)
This study examines on Celebrity Endorsement and Customers Buying Behaviour. The results were collected from 346 numbers of respondents through a questionnaires. A survey consisting of 25 questions that uses a Likert Scale questions to establishing measurable values from the respondents. The data analysis intends to determine whether there are significant impact between the independent variables (Endorser Gender, Endorser Credibility, Endorser Attractiveness and Endorser Type) with the dependent variable (Customer Buying Behaviour). This study found that there were only three from the independent variables (Endorser Gender, Endorser Attractiveness and Endorser Type) has significant effect where by only one independent variable (Endorser Credibility) has insignificant effect with the dependent variable (Customer Buying Behaviour). The data has been analyzed by using SPSS software.